Music in Korea : experiencing music, expressing culture - Kwon, Donna Lee (Global music series., 2012)
"Music in Korea is the first brief, single-volume text to provide a thematic, succinct introduction to the music of Korea--a region whose volatile political climate has often overshadowed its rich cultural and musical traditions. Based on author Donna Lee Kwon's extensive fieldwork, the text features interviews with performers, eyewitness accounts of performances, and vivid illustrations. Kwon uses three themes--Korea as a transnational player in East Asia, the intersection of Korean music and cultural politics, and Korea's maintenance of its strong cultural identity through both musical and aesthetic continuity--to survey the region and draw parallels and contrasts between its various traditions"--Cover, p. [4].